The monothiol single-domain glutaredoxin is conserved in the highly reduced mitochondria of Giardia intestinalis - Rada, Petr; Smíd, Ondrej; Sutak, Robert; Dolezal, Pavel; Pyrih, Jan; Zársky, Vojtech; Montagne, Jean-Jacques; Hrdy, Ivan; Camadro, Jean-Michel; Tachezy, Jan (Eukaryotic cell, 2009)
The highly reduced mitochondria (mitosomes) of Giardia intestinalis are recently discovered organelles for which, it was suggested, iron-sulfur cluster assembly was their only conserved function. However, only an incomplete set of the components required for FeS cluster biogenesis was localized to the mitosomes. Via proteomic analysis of a mitosome-rich cellular fraction together with immunofluorescence microscopy, we identified a novel mitosomal protein homologous to monothiol glutaredoxins containing a CGFS motif at the active site. Sequence analysis revealed the presence of long nonconserved N-terminal extension of 77 amino acids, which was absent in the mature protein. Expression of the complete and N-terminally truncated forms of the glutaredoxin indicated that the extension is involved in glutaredoxin import into mitosomes. However, the mechanism of preprotein processing is unclear, as the mitosomal processing peptidase is unable to cleave this type of extension. The recombinant mature protein was shown to form a homodimeric structure, which binds a labile FeS cluster. The cluster is stabilized by glutathione and dithiothreitol. Phylogenetic analysis showed that giardial glutaredoxin is related to the mitochondrial monothiol glutaredoxins involved in FeS cluster assembly. The identification of a mitochondrial-type monothiol glutaredoxin in the mitosomes of G. intestinalis thus completes the mitosomal FeS cluster biosynthetic pathway and provides further evidence for the mitochondrial origin of these organelles.
Keywords: glutaredoxiny; aminokyselinové motivy; vazebná místa; Binding Sites; Glutaredoxins; Microscopy, Fluorescence; Sequence Alignment; sekvence aminokyselin; mitochondrie; Amino Acid Sequence; sekvenční seřazení; Giardia lamblia; Phylogeny; Amino Acid Motifs; fluorescenční mikroskopie; Mitochondria; fylogeneze